Zina Act Review from Islamic Law in Bandar Sinembah Village Tanjung Morawa - Syarifah Syarifah (International Journal of Ethno-Sciences and Education Research, 2021)
Zina is an illegal sexual relationship carried out by a man and a woman outside the marriage bond. The prohibition of adultery, both contained in the Qur'an and hadith, in addition to enjoining good and evil, is also intended to maintain offspring and/or honor. Humans were created by Allah SWT as cultural creatures (civilized). As a cultured creature, the biological impulses of humans are arranged in such a way with various living institutions. Even though humans are biological creatures, human sex life is different from animal sex behavior. The definition of adultery according to Islamic law is different from the meaning of adultery (overspel/adultery) in the Indonesian Criminal Code, or adultery in the Pakistan Criminal Code and the Indian Criminal Code. One of the primary objectives of Islamic law, (maqosid al-Shariah) is to protect offspring, human honor and human existence. It is not easy to prove the occurrence of adultery. To accuse someone of adultery requires at least four witnesses who saw the act. (Surat an-Nuur verse 4). In order to impose sanctions/criminal stoning (Sura An-Nuur verse 2-3) and (Sura An-Nissa verse 15) according to the principle of Legi a posterior derogat legi a priori, the punishment for stoning in the hadith has been included by Surah An-Nuur verse 2-3 and Surah An-Nissa verse 15. This study uses a descriptive qualitative method, with the aim of providing an overview and knowledge to the Muslim community in the village of Bandar Sinembah, Tanjung Morawa. Before the research was conducted, it was found that the people in the village of Bandar Sinembah, Tanjung Morawa, which consisted of multi-ethnic groups did not fully understand the meaning of adultery according to Islamic teachings due to their low and lack of knowledge about the religion of Islam. After doing research and approaches, the village of Bandar Sinembah has begun to understand the meaning of adultery according to Islamic teachings, and now slowly they have left this bad habit.